The journey to truth is an experience - Giussani, Luigi (McGill-Queen's University Press, 2006)
As a young priest, Luigi Giussani was troubled by Catholicism's inability to effectively deal with secularism or laicism. In 1954 he began to develop a vision of faith rooted in experience. His ideas resonated with students and led to the birth of the Gioventù Studentesca (Student Youth) movement. Known today as Communion and Liberation, the movement is flourishing in Italy and around the world, including Canada, the United States, Brazil, Uganda, and Britain.